2005
DOI: 10.1088/0957-4484/16/8/028
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characterizations of multi-layered and multi-stacked PbSe quantum dots

Abstract: A multi-layered nanocomposite thin film was fabricated to increase the density of PbSe quantum dots. It consisted of low-loss polymer layers and multi-stacked PbSe quantum dot layers in series. The solutions of a UV-curable low-loss polymer and PbSe quantum dots were spin-coated layer-by-layer. An arrayed and multi-stacked PbSe quantum dot layer was self-assembled by spin-coating and solvent evaporation. The multi-stacked layers of PbSe quantum dots have a face-centred cubic structure with an average {111} pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…In general, the long lifetimes in Pb chalcogenide NCs are attributed to the effect of internal dielectric screening on the radiative recombination rate 11d. 21 In films, the oleate‐capped NCs exhibit much shorter radiative lifetimes ( τ 1/e =29 ns, see the http://www.wiley-vch.de/contents/jc_2002/2008/z705604_s.pdf) similar to those previously reported for PbS11c and PbSe NCs 22. This observation can be attributed to an increase of nonradiative recombination as a result of interparticle charge‐ and energy‐transfer processes23 and/or through the surface traps formed upon film preparation 24.…”
supporting
confidence: 82%
“…In general, the long lifetimes in Pb chalcogenide NCs are attributed to the effect of internal dielectric screening on the radiative recombination rate 11d. 21 In films, the oleate‐capped NCs exhibit much shorter radiative lifetimes ( τ 1/e =29 ns, see the http://www.wiley-vch.de/contents/jc_2002/2008/z705604_s.pdf) similar to those previously reported for PbS11c and PbSe NCs 22. This observation can be attributed to an increase of nonradiative recombination as a result of interparticle charge‐ and energy‐transfer processes23 and/or through the surface traps formed upon film preparation 24.…”
supporting
confidence: 82%
“…In general, the long lifetimes in Pb chalcogenide NCs are attributed to the effect of internal dielectric screening on the radiative recombination rate 11d. 21 In films, the oleate‐capped NCs exhibit much shorter radiative lifetimes ( τ 1/e =29 ns, see the http://www.wiley-vch.de/contents/jc_2001/2008/z705604_s.pdf) similar to those previously reported for PbS11c and PbSe NCs 22. This observation can be attributed to an increase of nonradiative recombination as a result of interparticle charge‐ and energy‐transfer processes23 and/or through the surface traps formed upon film preparation 24.…”
supporting
confidence: 82%
“…Our PbSe nanocrystals exhibit photoluminescence quantum efficiency up to 40% in solution for emission at 1.55 μm, while the efficiency reduces to a few percent in drop-cast solid form . We found that monolayer coverages of PbSe nanocrystals grafted on H-terminated Si are emissive for several months when kept in vacuum.…”
mentioning
confidence: 82%